2021
DOI: 10.1186/s13034-021-00362-w
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcome of manualised behavior therapy of chronic tic disorders in children and adolescents

Abstract: Background Chronic tic disorders are neurodevelopmental disorders that can be treated with Habit Reversal Training (HRT) and Exposure Response Prevention (ERP). Intermediate and long-term effects have been examined after individual treatment with HRT, whereas evaluation of long-term outcome after an initial treatment with ERP, or a combination of HRT and ERP is lacking. The present study examines the long-term effect after a combined treatment with HRT and ERP delivered in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Effect sizes were not reported Rizzo et al (2018) [ 14 ] BT vs. PE PT vs. PE BT vs. PT N = 110 Age 8–17 YGTSS-TTS : BT: 19.8 (pre) to 11.4 (post) PT: 24.1 (pre) to 15.7 (post) PE: 22.0 (pre) to 21.7 (post) FU : YGTSS-TTS at 3 months post BT/PE and 5 months post initiation of PT: BT: 12.4 PT: 14.7 PE: 20.7 Duration : 8 sessions (weekly, first two sessions 1.5 h, remaining sessions 1 h) Interventions : BT included HRT or ERP; PT included risperidone, aripiprazole or pimozide Results : Significant between-group effects on the YGTSS-TTS for BT vs. PE and PT vs. PE (in favor of BT and PT) Limitations : Uncertain whether the study was powered to detect significant between-group effects between BT and PT. Effect sizes were not reported Andrén et al (2019) [ 59 ] Internet ERP vs. Internet HRT N = 23 Age 8–16 YGTSS-TTS : Internet ERP: 23.8 (pre) to 18.3 (3FU) Within-group effect size: 1.12 Internet HRT: 23.5 (pre) to 20.2 (3FU) Within-group effect size: 0.50 12FU : YGTSS-TTS: Internet ERP: 16.9 Internet HRT: 19.4 Duration : 10 weeks of therapist-supported (via text messages) internet-delivered treatment Interventions : In addition to the ERP or HRT core elements, both groups included functional analysis and parent training Design : Study did not aim to compare groups Results : Significant within-group effect on the YGTSS-TTS for the Internet ERP group, but not the Internet HRT group Follow-up : Effects were maintained at 12FU Nissen et al (2019, 2021) [ 43 , 52 ] Individual HRT + ERP vs Group HRT + ERP N = 59 Age 9–17 YGTSS-TTS : Individual HRT + ERP: 23.8 (pre) to 14.3 (post) Within-group effect size: 1.21 Group HRT + ERP: 23.4 (pre) to 15.9 (post) Within-group effect size: 1.38 12FU : YGTSS-TTS: Individual HRT + ERP: 12.7 Group HRT + ERP: 12.8 Duration : 8 regular sessions and 1 booster session, delivered individually or in a group format Results : No significant between-group effect on the YGTSS-TTS. Significant within-group effects on the YGTSS-TTS for each group Follow-up ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect sizes were not reported Rizzo et al (2018) [ 14 ] BT vs. PE PT vs. PE BT vs. PT N = 110 Age 8–17 YGTSS-TTS : BT: 19.8 (pre) to 11.4 (post) PT: 24.1 (pre) to 15.7 (post) PE: 22.0 (pre) to 21.7 (post) FU : YGTSS-TTS at 3 months post BT/PE and 5 months post initiation of PT: BT: 12.4 PT: 14.7 PE: 20.7 Duration : 8 sessions (weekly, first two sessions 1.5 h, remaining sessions 1 h) Interventions : BT included HRT or ERP; PT included risperidone, aripiprazole or pimozide Results : Significant between-group effects on the YGTSS-TTS for BT vs. PE and PT vs. PE (in favor of BT and PT) Limitations : Uncertain whether the study was powered to detect significant between-group effects between BT and PT. Effect sizes were not reported Andrén et al (2019) [ 59 ] Internet ERP vs. Internet HRT N = 23 Age 8–16 YGTSS-TTS : Internet ERP: 23.8 (pre) to 18.3 (3FU) Within-group effect size: 1.12 Internet HRT: 23.5 (pre) to 20.2 (3FU) Within-group effect size: 0.50 12FU : YGTSS-TTS: Internet ERP: 16.9 Internet HRT: 19.4 Duration : 10 weeks of therapist-supported (via text messages) internet-delivered treatment Interventions : In addition to the ERP or HRT core elements, both groups included functional analysis and parent training Design : Study did not aim to compare groups Results : Significant within-group effect on the YGTSS-TTS for the Internet ERP group, but not the Internet HRT group Follow-up : Effects were maintained at 12FU Nissen et al (2019, 2021) [ 43 , 52 ] Individual HRT + ERP vs Group HRT + ERP N = 59 Age 9–17 YGTSS-TTS : Individual HRT + ERP: 23.8 (pre) to 14.3 (post) Within-group effect size: 1.21 Group HRT + ERP: 23.4 (pre) to 15.9 (post) Within-group effect size: 1.38 12FU : YGTSS-TTS: Individual HRT + ERP: 12.7 Group HRT + ERP: 12.8 Duration : 8 regular sessions and 1 booster session, delivered individually or in a group format Results : No significant between-group effect on the YGTSS-TTS. Significant within-group effects on the YGTSS-TTS for each group Follow-up ...…”
Section: Resultsmentioning
confidence: 99%
“…There was no statistically significant difference between the groups, apart from the YGTSS Impairment Score (in favor of the individual setting). The within-group treatment effects were maintained for both groups at a 12-month follow-up [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…One behavioral therapy is in line with the results of our study. In it, 47 TD children and adolescents were re-examined 1 year after manualized treatment, and the outcome demonstrated that none of the scores, namely the PUTS score, BATS score, CBCL, SCARED score, or MFQ score, differed when comparing the therapeutic patients and nontherapeutic patients at 12 months [ 20 ]. These two questionnaires may be the reason for the large standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies consist of exposure and response prevention (ERP), habit reversal therapy (HRT), or its descendant comprehensive behavioral interventions for tics (CBIT) 99 . A randomized control trial evaluating the long-term effect of both HRT and ERP in children and adults with tic disorders showed that the benefit of the therapies persisted at the 1-year follow-up visit in 74% of participants 100 . Despite robust evidence of the behavioral therapies to reduce tic frequency and severity and diminish the urges, finding a trained therapist can be challenging.…”
Section: Treatmentmentioning
confidence: 99%